Bez śladu. Niewyjaśnione przypadki zaginięć - Jurkiewicz, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
This article concerns unsolved missing people cases in Poland. It also shows the work of the ITAKA Foundation — Center For Missing People, the only NGO in Poland which works in the field of missing persons. It covers 5 different stories concerning un-solved missing persons cases from the late 1990s and 2000s, 4 of them describe mysteri-ous disappearances of children and teenagers which until today still remain unsolved.
Keywords: zaginieni; zaginione dzieci i młodzież; poszukiwanie osób zaginionych; nierozwiązane sprawy; zagadki kryminalne